Implementation of Swallowing Therapy in Dysphagia Patients with Ischemic Stroke Diagnosis - Nur Asnah Sitohang; Icceng Sidabutar (GLOBAL HEALTH SCIENCE GROUP, 2026)
Ischemic stroke is the acute onset of focal neurological deficits in vascular territories affecting the brain, retina or spinal cord due to cerebrovascular disease. The symptoms of stroke in general are partial or complete limb weakness, decreased cognitive function, difficulty swallowing or dysphagia, aphasia and dysarthria. Dysphagia is a swallowing disorder in which food and drinks take time to reach the stomach from the mouth. One of the interventions that can be given to patients is swallowing therapy. The purpose of this case study is to provide nursing care for ischemic stroke patients who experience dysphagia to overcome swallowing difficulties. This exercise requires patient participation by giving instructions or directions to patients both verbally and visually about how to swallow to increase swallowing muscle strength. There was one participant in the ischemic stroke patient. The exercise was given for 4 days 3 times a day for 15 minutes each exercise using the Mann Assessment of Swallowing Ability, a standardized instrument with established validity and reliability for dysphagia assessment in stroke patients. The results of the evaluation showed an improvement in the patient’ swallowing ability, namely before the intervention MASA 147 and after the intervention MASA 170. The application of swallowing exercises can be used as a nurse intervention in carrying out nursing actions independently for patients who experience swallowing disorders in ischemic stroke patients and can be continued by families at home.